Burma's path to democracy : the military, Aung San Suu Kyi and the Rohingya - Delphin, TinTin, 1948- (Algora Publishing, 2020)
"Burma is a country in transition: from monarchy to British colony, from independence to military dictatorships, and from the Generals to the Lady, Aung San Suu Kyi. This book traces one of the longest civil wars in history. It's about the Rohingya, one of the most persecuted people on earth. It's about pro-democracy uprisings, about sacrifice, and above all, the human resilience and capacity for hope. The book is based on true events and provides unique firsthand insights into key players in this enigmatic and troubled nation"--